2020
DOI: 10.7759/cureus.8170
|View full text |Cite
|
Sign up to set email alerts
|

National Institutes of Health Funding in Obstetrics and Gynecology: Analysis of R01 Grants by Degree and Gender

Abstract: Berg et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Another limiting factor in the advancement of women to high academic positions is the amount of third-party funding. In disciplines with many men physicians such as radiology and surgery, studies showed lower chances of women postdoctoral applicants for NIH funding [ 25 , 26 ], whereas, in the FP-dominated fields gynecology and pediatrics, the percentage of accepted applications from women was higher [ 27 ]. This suggests that the acceptance rate may also be influenced by the absolute number of applications from each gender.…”
Section: Discussionmentioning
confidence: 99%
“…Another limiting factor in the advancement of women to high academic positions is the amount of third-party funding. In disciplines with many men physicians such as radiology and surgery, studies showed lower chances of women postdoctoral applicants for NIH funding [ 25 , 26 ], whereas, in the FP-dominated fields gynecology and pediatrics, the percentage of accepted applications from women was higher [ 27 ]. This suggests that the acceptance rate may also be influenced by the absolute number of applications from each gender.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in average funding in current and constant dollars for the R01-equivalent grant awarded to women also increased slightly more than their male counterparts. A study revealed that women with an MD degree were awarded larger NIH R01 grants in obstetrics and gynecology than males with an MD degree between 2008 and 2017 [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have shown that very few osteopathic physicians serve as either the first or senior author in published original research manuscripts in emergency medicine, obstetrics and gynecology, pediatrics, and neurosurgery [1][2][3][4]. Additionally, no osteopathic physicians have been awarded a National Institutes of Health (NIH) R01 grant in emergency medicine, family medicine, general surgery, or obstetrics and gynecology in the previous decade [5][6][7][8]. Although we do not anticipate substantial differences in grants awarded to internal medicine investigators, no data currently exist on the scholarly activity between osteopathic and allopathic physicians within the specialty of internal medicine.…”
Section: Introductionmentioning
confidence: 99%